The Big Five Personality Traits Effect on Average Promotion and High Status Promotion in the IEC - Yaron BARUCH; Nicolae BIBU (Revista de Management Comparat International)
This article discusses the research results of the effect of the Big Five personality traits on promotion of human resources in the Israeli Electric Corporation (IEC) and tested if the same characteristics have the save effect throughout the entire individual career of an employee. The research method was quantitative. Each participant in this research filled a questionnaire about his own personality traits and his own promotion level in the same large organisation. From the data gathered the effect of each trait became clear both on the average time it took the employee to achieve each promotion status and the time it took the employee to reach his final status level. The study results showed that some personality traits had an opposite effect on average promotion time than the last status time.